Visual determination of malachite green in sea fish samples; Food Chemistry; Vol. 274 - Gavrilenko N. A. Natalia Airatovna; Volgina T. N. Tatiana Nikolaevna; Pugachev E. V. Evgeny Vyacheslavovich; Gavrilenko M. A. Mikhail Alekseevich (2019, 2019)
Title screen